Structural Asymmetry and Collaboration Gap: A Qualitative Case Study Approach to Pentahelix E-Government Implementation in Indonesian Local Government - Akbar Muhammad Nur; Alyani Muh. Khair Nurmahdy; Nusri Andi Zulkifli; Nursakti; Muhammad Iqbal (Journal of Vocational, Informatics and Computer Education, 2026)
Purpose - This study aims to empirically investigate how Pentahelix collaboration is structured and operationalized in the implementation of E-Government in Soppeng Regency, Indonesia, identify the enabling factors and barriers within the collaborative ecosystem, and evaluate its perceived impacts on local governance and public service delivery. Methods - This study employs a qualitative research design with a single-case study approach. Data were collected from February to April 2025 using three complementary methods: semi-structured in-depth interviews with 25 key informants representing all five Pentahelix stakeholder groups, non-participant observation of coordination meetings and public service points, and document analysis of E-Government roadmaps, policy regulations, and annual reports. Findings -The findings reveal that while the Pentahelix framework contributes to strengthening digital infrastructure and human resource capacity, collaboration remains structurally asymmetric and informal. Academia contributes research and training reactively, the Business sector engages transactionally as vendors, Media serves primarily as a one-way information broadcaster, and the Community participates passively as end-users rather than co-design partners. Persistent challenges include unequal internet access, variable public participation, and a pervasive "collaboration gap" a disconnect between multi-stakeholder inputs and their integration into a coherent transformative strategy. Research Implications – This study demonstrates that the effectiveness of Pentahelix collaboration in E-Government depends on the quality of interaction and integration mechanisms among stakeholders, not merely their formal inclusion, thereby shifting the research focus toward examining collaboration depth, coordination structures, and feedback systems. Originality – This study introduces the novel concept of the “collaboration gap,” providing empirical evidence of the disconnect between multi-stakeholder presence and functional integration while bridging collaborative governance and technology adoption theories in a single analytical framework.